Use of electronic technologies in the University of the Philippines Diliman Libraries and its effects on users' information needs - Laxamana, Evelyn O. (2002)
This study was conducted to determine the following: (1) users needs and expectations in the use of electronic resources, (2) accessibility and availability of these resources to users, (3) obstacles faced in using these resources, and (4) users' degree of satisfaction in their use of the UP Diliman Library System Resources.